Accumulation and toxicity of multi-walled carbon nanotubes in Xenopus tropicalis tadpoles. (October 2020) - Zhao, Jianbin; Xie, Guangyan; Xu, Yanbin; Zheng, Li; Ling, Jiayin
Abstract: Multi-walled carbon nanotubes (MWCNTs), a common nanomaterial widely used and discharged in environment, might exert toxic effects on aquatic animals. In this paper, filter-feeding tadpole of Xenopus tropicalis was selected as bioindicator to study the exposure effects of MWCNTs suspensions of 0.5, 1, 2, 4 and 8 mg/L for 72 h. The results showed that the tadpoles could remain high survival rate of over 96.7% after 24 h's exposure to MWCNTs, but then decrease considerably, showing a significant time-dependent relationship. The LC50 was 2.53 mg/L for tadpoles exposed to MWCNTs for 72 h, when MWCNTs accumulated in their gills and digestive tracts. Moreover, the enrichment degree of MWCNTs in tadpole was related to exposure density than time. When MWCNTs suspension concentration was not over 1 mg/L, the heart rates increased significantly and then decreased continuously. The survivors from the toxicity test were transferred to fresh filtered water for recovery, but MWCNTs accumulated in the tadpoles' body didn't decrease obviously after 4 days. Although the maximum tadpoles survival rate of 80% was recorded in the exposure group of 0.5 mg/L MWCNTs, only 43.3% of the survivors could recover. Therefore, the final survival rate was negative related to the exposure densities of MWCNTs but positive related to the accumulating degree in tadpoles' body. The results demonstrated that MWCNTs exposure posed potential health risks to filter-feeding organisms by intake and accumulation in organs, which could provide useful information for the reasonable evaluation and scientific management of nanomaterials. Graphical abstract: Image 1 Highlights: Toxicity of MWCNTs to X. tropicalis tadpole rose quickly with stress time and density. Tadpoles easily ingested MWCNTs and accumulated them in gills and digestive tracts. More than 56.7% of tadpoles survivors died owing to MWCNTs keeping accumulating. Toxicity of nanomaterials to filter-feeding aquatic organisms should cause concern.